Opportunities And Challenges For Decentralized Governments In The Globalization Era: Lessons From Indonesia - Wijayanti, Yuliani; Fathurrahman, Reza (Publikasi Indonesia, 2024)
Globalization has been inevitable by the increasing use of technology which allows people and goods to travel across borders, easier, faster, and cheaper. The only way for a country to take benefit from globalization is to give greater autonomy to the regions inside the country to allow them to manage their own economic resources. However, decentralization comes with its own opportunities and challenges. Reflecting from Indonesia’s quarter century of experience, this paper concludes that there is no single formula that fits all local governments. Each local government still needs clear direction, clarity in leadership, budget accountability, and transparency to optimize the benefit of globalization for the welfare of the people.